2019
DOI: 10.1111/ctr.13517
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as a risk factor for patient survival after kidney transplantation: A prospective observational cohort study

Abstract: Background: Short-term survival after kidney transplantation is excellent, but longterm survival remains low and is equivalent to non-end-stage renal disease patients with many invasive malignancies. The aim of the study was to explore vitamin D status in the early phase after transplantation as a prognostic marker for long-term graft and patient survival. Methods: All first-time kidney transplant recipients between October 2007 and October 2012 in Norway were included. Vitamin D was measured 10 weeks posttran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 41 publications
2
34
2
Order By: Relevance
“…The majority of patients from nephrology at RMH were treated for chronic kidney disease (CKD). Vitamin D levels are generally low in these patients, as CKD is associated with low levels of vitamin D, especially in patients with end-stage renal disease and kidney transplant recipient 55–59. Our findings are consistent with results from previous studies that demonstrated the association between low vitamin D levels and CKD.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of patients from nephrology at RMH were treated for chronic kidney disease (CKD). Vitamin D levels are generally low in these patients, as CKD is associated with low levels of vitamin D, especially in patients with end-stage renal disease and kidney transplant recipient 55–59. Our findings are consistent with results from previous studies that demonstrated the association between low vitamin D levels and CKD.…”
Section: Discussionsupporting
confidence: 91%
“…Written informed consent was obtained from all patients before any data and biological material were included in the Norwegian Renal Registry and the biobank. Other analyses from the study have been presented previously (25)(26)(27). Included in this analysis were 900 consecutively transplanted adult kidney recipients in the period October 15, 2007, to October 18, 2012, from each of whom a 10-week blood sample was biobanked.…”
Section: Patientsmentioning
confidence: 99%
“…Out of these 196 articles 40 were eligible for full-text analysis. Ultimately, sixteen articles were included in this review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Figure 1 ). The rest of the articles were excluded as the design, protocol and/or methodology used investigated a different PICO question to those of our study.…”
Section: Resultsmentioning
confidence: 99%